Temperature Dependence of Electrical Properties and Crystal Structure of 0.29Pb(In1/2Nb1/2)O3–0.44Pb(Mg1/3Nb2/3)O3–0.27PbTiO3 Single Crystals - Qian Li; Yun Liu; Andrew Studer; Zhenrong Li; Ray Withers; Zhuo Xu (Advances in Condensed Matter Physics)
We characterized the temperature dependent (~25–200°C) electromechanical properties and crystal structure of Pb(In1/2Nb1/2)O3-Pb(Mg1/3Nb2/3)O3-PbTiO3 single crystals using in situ electrical measurement and neutron diffraction techniques. The results show that the poled crystal experiences an addition phase transition around 120°C whereas such a transition is absent in the unpoled crystal. It is also found that the polar order persists above the maximum dielectric permittivity temperature at which the crystal shows a well-defined antiferroelectric behavior. The changes in the electrical properties and underlying crystal structure are discussed in the paper.